Effect of oral health promotion interventions on pregnant women dental caries: a field trial - Marzie Deghatipour; Zahra Ghorbani; Amir Hossein Mokhlesi; Shahla Ghanbari; Mahshid Namdari (BMC, 2022)
Abstract Background Dental caries is a costly and very common disease, especially in pregnant women. Reasons such as not paying attention to oral health, poor diet and also lack of adequate education in this regard cause this to happen. Performing well-designed educational interventions using primary health system's forces, can improve oral health of pregnant women and help control this disease. We conducted this study to evaluate the effectiveness of some oral health interventions on pregnant women dental caries. Methods A field trial study was done in comprehensive Health Centers in Varamin, Tehran, Iran to assess 439 mothers' dental health status from pregnancy up to 2 years after delivery in intervention (n = 239) and control groups (n = 200). Mothers in intervention groups received oral health-related education consisted of nutritional and behavioral messages via either of four methods: A: comprehensive method including all following methods together (n = 74), B: group discussion by dentists (n = 59), C: face to face education by primary health care providers (n = 53), and D: social network applications (n = 53); while those in control group only received routine maternal and oral health care. We used a questionnaire to collect mothers' demographic, socioeconomic and dental care behavior data and also performed oral examinations to assess their DMFT at baseline and 24 months after delivery to evaluate the effectiveness of these educational oral health interventions. Results From 454 mothers participated the examination session, 18 pregnant women discontinued during the follow-ups and 439 were remained with mean age of 27.47. In the intervention group, the frequency of daily brushing among women increased from 64% at baseline to 85.6% at the last follow-up and the mean D significantly decreased nearly 1unit at same period (P < 0.05). Most and least dental caries changes were in comprehensive intervention group and social network intervention group compared to other intervention groups, respectively. Conclusions Performing educational interventions during and after pregnancy using various message delivery methods and messengers (oral health professionals and trained PHCPs), could improve oral health status and behaviors of pregnant and lactating mothers in a feasible and applicable manner.